Sulfur-based sodium ion battery, preparation method thereof and electric device
By loading sodium supplementation agents on the sodium ion positive electrode and separator, the problem of irreversible consumption of sodium ions during the first charging of the thio sodium ion battery is solved, and the discharge capacity, Coulomb efficiency and cycling performance of the battery are improved.
Patent Information
- Application Number
- CN202411994575.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-03-28
AI Technical Summary
During the first charging process of existing sodium sulfide ion batteries, the irreversible consumption of sodium ions leads to low efficiency, low discharge capacity and reduced energy density.
The sodium supplementation agent is loaded on the sodium ion positive electrode, and/or the sodium supplementation agent is loaded on the surface of the separator facing the sodium ion positive electrode to match the sulfur-carbon negative electrode to supplement the sodium ions that are irreversibly consumed on the negative electrode side during the first charging process.
The first discharge capacity, average Coulomb efficiency and cycling performance of sodium sulfhydryl ion batteries are improved.
Smart Images

Figure CN119725689A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of sodium ion batteries and relates to a sulfur-based sodium ion battery, and in particular to a sulfur-based sodium ion battery and a preparation method and an electric device thereof. Background Art
[0002] As an emerging battery technology, sodium-ion batteries have many advantages over traditional lithium-ion batteries in terms of economy, safety and environmental friendliness. If sodium metal is used as the negative electrode, its application will be limited by the manufacture and processing of sodium metal. In addition, the uneven deposition on the surface of the sodium metal electrode can easily cause dendrite growth, which will lead to an increase in the risk of short circuit and a decrease in battery performance, further hindering the feasibility of its commercial application. In order to avoid this problem, researchers have proposed a variety of alternatives; among them, carbon materials are used as the negative electrode active materials of sodium-ion batteries. Although the obtained carbon material negative electrode has good electrochemical properties, the production cost is high and the specific capacity is relatively low, which is not suitable for high-load scenarios. In addition, although metal sulfur, oxygen and nitride have good conductivity and stable cycle performance, they are also considered as negative electrode active materials for sodium-ion batteries. However, the synthesis process of these materials is complex, they are sensitive to moisture and air, and the presence of heavy metals reduces the energy density. In addition, the negative electrode-free design is also a solution to be considered. However, although the negative electrode-free design improves the energy density, it is easy to produce dendrites and "dead sodium", accompanied by serious side reactions. These issues have prompted further exploration of battery technology.
[0003] CN118352529A discloses a positive electrode pre-sodiumization reagent for preparing a high energy density sodium ion battery, a preparation method thereof and a pre-sodiumization method. The invention uses the pre-sodiumization reagent in a sodium ion positive electrode to hard carbon system, and supplements the irreversible capacity of the first cycle at a lower pre-sodium reagent decomposition potential. Although good cycle performance is obtained, the energy density cannot be further improved due to the limitations of the specific capacity and surface load of the negative electrode hard carbon.
[0004] CN117638229A discloses an electrolyte additive and electrolyte for a sodium ion battery without a negative electrode. The invention improves the interface stability of the electrode-electrolyte by adding sulfur / fluorine-containing ester solvents and fluorinated sodium salts as additives, effectively improving the efficiency of the first cycle and the cycle capacity retention rate. However, its first cycle coulomb efficiency is still low, mainly because there is no host on the negative electrode side to protect the sodium metal, and it is easy to generate dendrites, short circuit, and poor safety.
[0005] CN115332503A discloses a sodium ion battery hard carbon-molybdenum disulfide negative electrode material and its preparation method. In the invention, molybdenum disulfide is prepared by using a molybdenum source and a sulfur source, and sintered with hard carbon to prepare a sulfide negative electrode, which avoids volume expansion during the sodium storage process and improves the cycle performance of the sodium ion battery. However, its preparation method is complicated, and the introduction of metallic molybdenum elements in the process reduces the specific capacity of the negative electrode.
[0006] Sulfur-carbon materials with conversion reaction principle have obvious advantages as negative electrodes of sodium ion batteries. First, compared with carbon material negative electrodes, their specific capacity is higher, and sulfur resources are abundant and low-cost. Second, compared with metal sulfur / oxygen / nitride, they avoid the use of heavy metals and have advantages in cost and specific energy. Third, compared with metal sodium negative electrodes and no negative electrode design, they avoid the generation of sodium dendrites and have more stable cycle performance. Therefore, the sulfur-based sodium ion battery system based on sodium ion positive electrode active materials and sulfur-carbon negative electrode active materials has stronger competitiveness.
[0007] However, in practical applications, in order to give full play to the high specific capacity of the sulfur-carbon negative electrode and overcome the shuttle effect caused by the polysulfide solvent, a specific electrolyte composition is often required, and the first charging process will form a stable solid electrolyte membrane (SEI) on the sulfur-carbon negative electrode side. This process will consume a large amount of sodium ions, which will cause a large amount of sodium ions in the negative electrode side to be irreversibly consumed, resulting in the problems of too high first charging capacity, too low discharge capacity and too low first coulombic efficiency. At the same time, since the positive electrode side is in a sodium-deficient state after the first cycle, it will also cause a great decrease in the battery energy density.
[0008] The sulfur-based sodium ion batteries disclosed in the prior art all have certain defects. During the first charging process, sodium ions will escape from the positive electrode, which irreversibly consumes a large amount of sodium ions on the negative electrode side, causing a decrease in the coulombic efficiency of the battery and causing serious capacity decay. Therefore, it is very important to develop and design a new type of sulfur-based sodium ion battery and its preparation method and electric device. Summary of the invention
[0009] In view of the deficiencies in the prior art, the object of the present invention is to provide a sulfur-based sodium ion battery and a preparation method and an electric device thereof. The negative electrode in the sulfur-based sodium ion battery provided by the present invention is a sulfur-carbon negative electrode, which has a higher specific capacity, a lower cost, less environmental pollution and can avoid the generation of sodium dendrites; in addition, in the sulfur-based sodium ion battery provided by the present invention, a sodium supplement is loaded on the sodium ion positive electrode, and / or a sodium supplement is loaded on the surface of the side of the diaphragm facing the sodium ion positive electrode to match the sulfur-carbon negative electrode to prepare the sulfur-based sodium ion battery. The sodium supplement loaded on the sodium ion positive electrode and / or the sodium supplement loaded in the diaphragm can replenish the sodium ions that are irreversibly consumed on the negative electrode side during the first charging process, thereby improving the first discharge capacity, average coulomb efficiency and cycle performance of the sulfur-based sodium ion battery.
[0010] To achieve this object, the present invention adopts the following technical solutions:
[0011] In a first aspect, the present invention provides a sulfur-based sodium ion battery, wherein the negative electrode of the sulfur-based sodium ion battery is a sulfur-carbon negative electrode, the sodium ion positive electrode of the sulfur-based sodium ion battery is loaded with a sodium supplement, and / or the surface of the diaphragm of the sulfur-based sodium ion battery facing the sodium ion positive electrode is loaded with a sodium supplement.
[0012] The negative electrode in the sulfur-based sodium ion battery provided by the present invention is a sulfur-carbon negative electrode, which has a higher specific capacity, a lower cost, less environmental pollution and can avoid the generation of sodium dendrites; in addition, in the sulfur-based sodium ion battery provided by the present invention, a sodium supplementing agent is loaded on the sodium ion positive electrode, and / or a sodium supplementing agent is loaded on the surface of the side of the diaphragm facing the sodium ion positive electrode, so as to match the sulfur-carbon negative electrode to assemble the sulfur-based sodium ion battery, wherein the sodium supplementing agent loaded on the sodium ion positive electrode and / or the sodium supplementing agent loaded in the diaphragm can replenish the sodium ions that are irreversibly consumed on the negative electrode side during the first charging process, thereby improving the first discharge capacity, average coulomb efficiency and cycle performance of the sulfur-based sodium ion battery.
[0013] Preferably, the sodium supplement agent is loaded on the sodium ion positive electrode in the following ways: distributed in the positive electrode material layer of the sodium ion positive electrode, and / or coated on the surface of the positive electrode material layer of the sodium ion positive electrode facing the diaphragm, and / or coated between the positive electrode material layer of the sodium ion positive electrode away from the diaphragm and the positive electrode current collector.
[0014] Preferably, the membrane comprises any one or a combination of at least two of a polypropylene membrane, a cellulose membrane, a polyethylene membrane, a glass fiber membrane or an oxide coating membrane. Typical but non-limiting combinations include a combination of a polypropylene membrane and a cellulose membrane, a combination of a glass fiber membrane and an oxide coating membrane, or a combination of a polypropylene membrane, a cellulose membrane and a polyethylene membrane, preferably a glass fiber membrane.
[0015] Preferably, the mass of the sodium supplement is 5-30% of the mass of the positive electrode active material in the sodium ion positive electrode, for example, it can be 5%, 7%, 10%, 12%, 15%, 17%, 20%, 22%, 25%, 27% or 30%, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable, preferably 8-12%.
[0016] Preferably, the sodium supplement includes any one of metallic sodium powder, Na2S, Na2O, Na2C4O4, Na2C6O6, Na5TaO5, Na2C6H2O6, Na5VO5, NaNH2, Na2C2O4, Na2CO3, Na3VO4 or NaHF2, or a combination of at least two thereof. Typical but non-limiting combinations include a combination of metallic sodium powder and Na2S, a combination of Na2O and Na2C4O4, a combination of Na2C6O6 and Na5TaO5, a combination of Na2C6H2O6 and Na5VO5, a combination of NaNH2 and Na2C2O4, a combination of Na2CO3 and Na3VO4, a combination of Na3VO4 and NaHF2, or a combination of metallic sodium powder, Na2S and Na2O.
[0017] Preferably, the sodium ion positive electrode comprises a positive electrode current collector and a positive electrode material layer covering the surface of the positive electrode current collector, and the positive electrode material layer comprises a sodium ion active material, a positive electrode conductive agent and a positive electrode binder.
[0018] Preferably, the mass ratio of the sodium ion active material, the positive electrode conductor and the positive electrode binder in the positive electrode material layer is (55-99):(0.5-15):(1-20).
[0019] The mass ratio of the sodium ion active material to the positive electrode conductive agent in the positive electrode material layer of the present invention is (55-99):(0.5-15), for example, it can be 55:0.5, 55:0.7, 55:3, 55:7, 55:13, 55:15, 67:0.5, 67:0.7, 67:3, 67:7, 67:13, 67:15, 77:0.5, 77:3, 77:13, 77:15, 87:0.5, 87:0.7, 87:3, 87:7, 87:13, 87:15, 99:0.5, 99:0.7, 99:7 or 99:13, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0020] The mass ratio of the sodium ion active material to the positive electrode binder in the positive electrode material layer of the present invention is (55-99):(1-20), for example, it can be 55:1, 55:3, 55:7, 55:13, 55:17, 55:20, 67:1, 67:3, 67:7, 67:13, 67:17, 67:20, 77:1, 77:3, 77:13, 77:17 or 77:20, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0021] Preferably, the sodium ion active material includes sodium copper iron manganese oxide, sodium vanadium phosphate, sodium vanadium fluorophosphate, sodium iron sulfate, sodium iron pyrophosphate, Na2MnO2, Na3MnO2, NaFe 0.5 Ni 0.5 O2、NaNi 0.05 Mn 0.95 Fe[(CN)6] or Na2Mn[MnFe(CN)6], or a combination of at least two thereof, typical but non-limiting combinations include a combination of sodium copper iron manganate and sodium vanadium phosphate, a combination of sodium vanadium fluorophosphate and sodium iron sulfate, a combination of sodium iron pyrophosphate and Na2MnO2, a combination of Na3MnO2 and NaFe 0.5 Ni 0.5 Combination of O2, NaNi 0.05 Mn 0.95 A combination of Fe[(CN)6] or Na2Mn[MnFe(CN)6], or a combination of sodium copper iron manganate, sodium vanadium phosphate and sodium vanadium fluorophosphate.
[0022] Preferably, the positive electrode conductive agent includes any one of conductive carbon black, acetylene black, Ketjen black, graphene or carbon nanotubes, or a combination of at least two of them. Typical but non-limiting combinations include a combination of conductive carbon black and acetylene black, a combination of Ketjen black and graphene, a combination of graphene and carbon nanotubes, or a combination of conductive carbon black, acetylene black and Ketjen black.
[0023] Preferably, the positive electrode binder includes any one of sodium carboxymethyl cellulose, polyacrylonitrile, polyacrylic acid, polyvinylidene fluoride, polyvinyl pyrrolidone or styrene-butadiene rubber, or a combination of at least two of them. Typical but non-limiting combinations include a combination of sodium carboxymethyl cellulose and polyacrylonitrile, a combination of polyacrylic acid and polyvinylidene fluoride, a combination of polyvinyl pyrrolidone and styrene-butadiene rubber, or a combination of sodium carboxymethyl cellulose, polyacrylonitrile and polyacrylic acid.
[0024] Preferably, the sulfur-carbon negative electrode comprises a negative electrode current collector and a negative electrode material layer covering the surface of the negative electrode current collector, and the negative electrode material comprises a sulfur-carbon composite material, a negative electrode conductive agent and a negative electrode binder.
[0025] Preferably, the mass ratio of the sulfur-carbon composite material, the negative electrode conductive agent and the negative electrode binder in the negative electrode material layer is (50-99):(0.5-30):(1-20).
[0026] The mass ratio of the sulfur-carbon composite material to the negative electrode conductive agent in the negative electrode material layer of the present invention is (50-99):(0.5-30), for example, it can be 50:0.5, 50:3, 50:7, 50:13, 50:17, 50:23, 50:27, 50:30, 77:0.5, 77:3, 77:13, 77:17, 77:23, 77:27, 77:30, 99:0.5, 99:3, 99:7, 99:13, 99:17, 99:23 or 99:30, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0027] Preferably, the sulfur-carbon composite material includes a carbon-containing material, and sulfur and / or sulfide. The mass ratio of the carbon-containing material to the sulfur and / or sulfide in the sulfur-carbon composite material is (0.2-2):1, for example, it can be 0.2:1, 0.3:1, 0.4:1, 0.5:1, 0.6:1, 0.7:1, 0.8:1, 0.9:1, 1:1, 1.1:1, 1.2:1, 1.3:1, 1.4:1, 1.5:1, 1.6:1, 1.7:1, 1.8:1, 1.9:1 or 2:1, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0028] Preferably, the carbon-containing material includes any one of microporous carbon, conductive carbon black, acetylene black, Ketjen black, graphene, carbon nanotubes, two-dimensional transition metal carbides, carbon-containing metal organic framework materials, carbon-containing covalent organic framework materials or high-temperature carbonized organic matter, or a combination of at least two thereof. Typical but non-limiting combinations include a combination of microporous carbon and conductive carbon black, a combination of acetylene black and Ketjen black, a combination of graphene and carbon nanotubes, a combination of two-dimensional transition metal carbides and carbon-containing metal organic framework materials, a combination of carbon-containing covalent organic framework materials and high-temperature carbonized organic matter, or a combination of microporous carbon, conductive carbon black and acetylene black.
[0029] Preferably, the sulfide includes any one of polyacrylonitrile sulfide, ferrous sulfide, ferric disulfide, copper sulfide, cuprous sulfide, nickel sulfide, cobalt sulfide or molybdenum disulfide, or a combination of at least two thereof. Typical but non-limiting combinations include a combination of polyacrylonitrile sulfide and ferrous sulfide, a combination of ferrous sulfide and ferric disulfide, a combination of copper sulfide and cuprous sulfide, a combination of nickel sulfide and cobalt sulfide, a combination of cobalt sulfide and molybdenum disulfide, or a combination of ferrous sulfide, ferric disulfide and copper sulfide.
[0030] Preferably, the negative electrode conductive agent includes any one of conductive carbon black, acetylene black, Ketjen black, graphene or carbon nanotubes, or a combination of at least two of them. Typical but non-limiting combinations include a combination of conductive carbon black and acetylene black, a combination of Ketjen black and graphene, a combination of graphene and carbon nanotubes, or a combination of conductive carbon black, acetylene black and Ketjen black.
[0031] Preferably, the negative electrode binder includes any one of sodium carboxymethyl cellulose, polyacrylonitrile, polyacrylic acid, polyvinylidene fluoride, polyvinyl pyrrolidone or styrene-butadiene rubber, or a combination of at least two of them. Typical but non-limiting combinations include a combination of sodium carboxymethyl cellulose and polyacrylonitrile, a combination of polyacrylic acid and polyvinylidene fluoride, a combination of polyvinyl pyrrolidone and styrene-butadiene rubber, or a combination of sodium carboxymethyl cellulose, polyacrylonitrile and polyacrylic acid.
[0032] Preferably, the sulfur-based sodium ion battery further includes an electrolyte and a casing.
[0033] Preferably, the electrolyte comprises a sodium salt and a solvent, and the solvent comprises any one or a combination of at least two of an ether solvent, an ester solvent or an ionic liquid solvent. Typical but non-limiting combinations include a combination of an ether solvent and an ester solvent, a combination of an ester solvent and an ionic liquid solvent, or a combination of an ether solvent, an ester solvent and an ionic liquid solvent.
[0034] Preferably, the concentration of sodium salt in the electrolyte is 0.5-10 mol / L, and the sodium salt includes any one of sodium trifluoromethanesulfonate, sodium hexafluorophosphate, sodium perchlorate, sodium tetrafluoroborate, sodium bis(trifluoromethylsulfonyl)imide, sodium bis(fluorosulfonyl)imide, sodium hexafluoroarsenate or sodium difluoro(oxalato)borate, or a combination of at least two thereof.
[0035] The concentration of sodium salt in the electrolyte of the present invention is 0.5-10 mol / L, for example, it can be 0.5 mol / L, 1 mol / L, 2 mol / L, 3 mol / L, 4 mol / L, 5 mol / L, 6 mol / L, 7 mol / L, 8 mol / L, 9 mol / L or 10 mol / L, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0036] Preferably, the ether solvent includes any one of ethylene glycol dimethyl ether, diethylene glycol dimethyl ether, ethylene glycol diethyl ether or tetraethylene glycol dimethyl ether, or a combination of at least two thereof. Typical but non-limiting combinations include a combination of ethylene glycol dimethyl ether and diethylene glycol dimethyl ether, a combination of ethylene glycol diethyl ether and tetraethylene glycol dimethyl ether, or a combination of ethylene glycol dimethyl ether, diethylene glycol dimethyl ether and ethylene glycol diethyl ether.
[0037] Preferably, the ester solvent includes any one of fluoroethylene carbonate, propylene carbonate, ethylene carbonate, ethyl methyl carbonate, diethyl carbonate or dimethyl carbonate, or a combination of at least two of them. Typical but non-limiting combinations include a combination of fluoroethylene carbonate and propylene carbonate, a combination of ethylene carbonate and ethyl methyl carbonate, a combination of diethyl carbonate and dimethyl carbonate, or a combination of fluoroethylene carbonate, propylene carbonate and ethylene carbonate, preferably fluoroethylene carbonate.
[0038] Preferably, the ionic liquid solvent includes any one of 1-ethyl-3-methylimidazoline bis(trifluoromethylsulfonyl)imide, 1-methyl-3-hexylimidazoline bis(trifluoromethylsulfonyl)imide salt, 1-methyl-1-propylpyrrolidine bis(trifluoromethylsulfonyl)imide salt or 1-methyl-1-propylpyrrolidinium bis(fluorosulfonyl)imide or a combination of at least two thereof, and a typical but non-limiting combination includes 1-ethyl-3-methylimidazoline bis(trifluoromethylsulfonyl)imide and 1-methyl-3-hexylimidazoline bis(trifluoromethylsulfonyl)imide. The invention also includes a combination of 1-methyl-3-hexylimidazoline bis(trifluoromethylsulfonyl)imide salt and 1-methyl-1-propylpyrrolidine bis(trifluoromethylsulfonyl)imide salt, a combination of 1-methyl-1-propylpyrrolidine bis(trifluoromethylsulfonyl)imide salt and 1-methyl-1-propylpyrrolidinium bis(fluorosulfonyl)imide salt, or a combination of 1-ethyl-3-methylimidazoline bis(trifluoromethylsulfonyl)imide, 1-methyl-3-hexylimidazoline bis(trifluoromethylsulfonyl)imide salt and 1-methyl-1-propylpyrrolidinium bis(trifluoromethylsulfonyl)imide salt.
[0039] Preferably, the electrolyte comprises a locally high-concentration electrolyte.
[0040] In a second aspect, the present invention provides a method for preparing the sulfur-based sodium ion battery according to the first aspect, the preparation method comprising:
[0041] A sulfur-carbon negative electrode comprising a sulfur-carbon composite material is prepared, a sodium ion positive electrode loaded with a sodium supplement is prepared, and the sulfur-carbon negative electrode, a separator and a sodium ion positive electrode loaded with a sodium supplement are assembled into a sulfur-based sodium ion battery;
[0042] or
[0043] A sulfur-carbon negative electrode comprising a sulfur-carbon composite material is prepared, and a diaphragm with a sodium supplement agent loaded on one side is prepared. The sulfur-carbon negative electrode, the diaphragm loaded with the sodium supplement agent and the sodium ion positive electrode are assembled into a sulfur-based sodium ion battery, and the surface of the side of the diaphragm loaded with the sodium supplement agent is directed toward the sodium ion positive electrode.
[0044] or
[0045] A sulfur-carbon negative electrode comprising a sulfur-carbon composite material is prepared, a diaphragm with a sodium supplement agent loaded on one side is prepared, and a sodium ion positive electrode loaded with the sodium supplement agent is prepared. The sulfur-carbon negative electrode, the diaphragm loaded with the sodium supplement agent, and the sodium ion positive electrode loaded with the sodium supplement agent are assembled into a sulfur-based sodium ion battery, and the surface of the diaphragm loaded with the sodium supplement agent is directed toward the sodium ion positive electrode.
[0046] In a third aspect, the present invention provides an electric device, comprising the sulfur-based sodium ion battery described in the second aspect.
[0047] The numerical range described in the present invention not only includes the point values listed above, but also includes any point values between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0048] Compared with the prior art, the present invention has the following beneficial effects:
[0049] The negative electrode in the sulfur-based sodium ion battery provided by the present invention is a sulfur-carbon negative electrode, which has a higher specific capacity, a lower cost, less environmental pollution and can avoid the generation of sodium dendrites; in addition, in the sulfur-based sodium ion battery provided by the present invention, a sodium supplementing agent is loaded on the sodium ion positive electrode, and / or a sodium supplementing agent is loaded on the surface of a side of the diaphragm facing the sodium ion positive electrode, so as to match the sulfur-carbon negative electrode to assemble the sulfur-based sodium ion battery, wherein the sodium supplementing agent loaded on the sodium ion positive electrode and / or the sodium supplementing agent loaded toward the diaphragm can replenish the sodium ions that are irreversibly consumed on the negative electrode side during the first charging process, thereby improving the first discharge capacity, average coulomb efficiency and cycle performance of the sulfur-based sodium ion battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0050] Figure 1 It is a schematic diagram of the structure of the sulfur-based sodium ion battery provided in Examples 1, 4, 6 to 11 and 17 to 19.
[0051] Figure 2 It is a schematic diagram of the structure of the sulfur-based sodium ion battery provided in Example 5 and Examples 12 to 16.
[0052] Figure 3 The figure is a curve showing the change of the discharge specific capacity and coulombic efficiency of the sulfur-based sodium ion battery provided in Example 1 with the number of cycles.
[0053] Figure 4 This is a curve showing the change of the discharge specific capacity and coulombic efficiency of the sulfur-based sodium ion battery provided in Example 1 with the number of cycles.
[0054] Among them, 1-negative electrode current collector; 2-negative electrode material layer; 3-positive electrode current collector; 4-positive electrode material layer; 5-diaphragm; 6-sodium supplement layer. DETAILED DESCRIPTION
[0055] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0056] Example 1
[0057] This embodiment provides a sulfur-based sodium ion battery, such as Figure 1 As shown, the negative electrode of the sulfur-based sodium ion battery is a sulfur-carbon negative electrode, and the positive electrode is a sodium ion positive electrode loaded with a Na2S sodium supplement;
[0058] The sulfur-carbon negative electrode comprises a negative electrode current collector 1 and a negative electrode material layer 2 covered on the surface of the negative electrode current collector 1, wherein the negative electrode material comprises a sulfur-carbon composite material (composed of conductive carbon black and S element in a mass ratio of 1:1) with a mass ratio of 80:10:10, acetylene black and sodium carboxymethyl cellulose;
[0059] The sodium ion positive electrode comprises a positive electrode current collector 3 and a positive electrode material layer 4 covered on the surface of the positive electrode current collector 3, wherein the positive electrode material layer 4 comprises sodium vanadium phosphate, acetylene black and polyvinylidene fluoride in a mass ratio of 80:10:10; the Na2S sodium supplement is distributed in the positive electrode material layer 4 of the sodium ion positive electrode, and the mass of the Na2S sodium supplement is 12.5% of the mass of the sodium vanadium phosphate in the sodium ion positive electrode;
[0060] The sulfur-based sodium ion battery further comprises a glass fiber separator 5, an electrolyte and a shell, wherein the electrolyte comprises sodium trifluoromethanesulfonate and fluoroethylene carbonate solvent with a concentration of 5 mol / L.
[0061] The preparation method of the sulfur-based sodium ion battery is:
[0062] (1) Preparation of sulfur-carbon negative electrode:
[0063] A mixture was obtained by mixing a sulfur element and conductive carbon black in a mass ratio of 1:1 by wet grinding at a rotation speed of 500 rpm, wherein the reagent used in the wet grinding process was ethanol; the obtained mixture was vacuum dried in an oven for 24 hours, then taken out, and then placed in a glove box (O2<1ppm, H2O<1ppm), and then heated to 155°C in a muffle furnace and stored for 15 hours to prepare a sulfur-carbon composite material;
[0064] 0.8 g of the obtained sulfur-carbon composite material was mixed with 0.1 g of acetylene black by hand grinding in a mortar for 20 min, and then added to 10 g of sodium carboxymethyl cellulose (CMC) glue (the solvent was H2O, and the mass fraction of CMC was 1 wt% based on the mass of the CMC glue), stirred overnight to form a uniform slurry; the obtained slurry was coated on a carbon-coated aluminum foil with a scraper with a height of 75 μm, and then placed in a vacuum oven for drying at a temperature set to 70°C and a drying time of 10 h to obtain a sheet, which was cut into discs with a diameter of 12 mm to obtain a sulfur loading of 0.4 mg / cm 2 Sulfur-carbon negative electrode;
[0065] (2) Preparation of sodium ion positive electrode loaded with sodium supplement:
[0066] 0.8 g of sodium vanadium phosphate, 0.1 g of acetylene black and 0.1 g of Na2S were mixed by hand grinding in a mortar for 20 min, and then 3.33 g of polyvinylidene fluoride (PVDF) glue (the solvent was N-methylpyrrolidone, and the mass fraction of PVDF was 3 wt % based on the mass of the PVDF glue) was added and stirred overnight to form a uniform slurry; the obtained slurry was coated on a carbon-coated aluminum foil with a scraper with a height of 350 μm, and then placed in a vacuum oven for drying at a temperature set at 70°C and a drying time of 10 h to obtain a sheet, which was cut into discs with a diameter of 12 mm to obtain a sodium vanadium phosphate loading of 5.9 mg / cm 2 The sodium ion positive electrode;
[0067] (3) Assembling the sulfur-carbon negative electrode obtained in step (1), the sodium ion positive electrode loaded with a sodium supplement agent obtained in step (2), the glass fiber separator 5 and the electrolyte to obtain a sulfur-based sodium ion battery with N / P (ratio of negative electrode capacity to positive electrode capacity) = 1.0.
[0068] Example 2
[0069] This embodiment provides a sulfur-based sodium ion battery, wherein the negative electrode of the sulfur-based sodium ion battery is a sulfur-carbon negative electrode, and the positive electrode is a sodium ion positive electrode loaded with a Na2C4O4 sodium supplement;
[0070] The sulfur-carbon negative electrode includes a negative electrode current collector and a negative electrode material layer covered on the surface of the negative electrode current collector, wherein the negative electrode material includes a sulfur-carbon composite material (composed of graphene, Na2S and S single substances in a mass ratio of 0.5:1:1) with a mass ratio of 70:25:5, acetylene black and polyacrylonitrile;
[0071] The sodium ion positive electrode comprises a positive electrode current collector and a positive electrode material layer covered on the surface of the positive electrode current collector, wherein the positive electrode material layer comprises sodium vanadium phosphate, acetylene black and polyacrylonitrile in a mass ratio of 70:15:20; the Na2C4O4 sodium supplement is loaded on a surface of the positive electrode material layer of the sodium ion positive electrode close to the diaphragm, and the mass of the Na2C4O4 sodium supplement is 30% of the mass of the sodium vanadium phosphate in the sodium ion positive electrode;
[0072] The sulfur-based sodium ion battery also includes an electrolyte and a shell, wherein the electrolyte includes sodium hexafluorophosphate with a concentration of 10 mol / L and 1-ethyl-3-methylimidazoline bis(trifluoromethylsulfonyl)imide solvent.
[0073] The preparation method of the sulfur-based sodium ion battery is:
[0074] (1) Preparation of sulfur-carbon negative electrode:
[0075] Graphene, Na2S, and S single substances in a mass ratio of 0.5:1:1 were mixed by wet grinding at a rotation speed of 500 rpm to obtain a mixture, wherein the reagent used in the wet grinding process was ethanol; the obtained mixture was vacuum dried in an oven for 24 hours, then taken out, and then placed in a glove box (O2<1ppm, H2O<1ppm), and then heated to 155°C in a muffle furnace and stored for 15 hours to prepare a sulfur-carbon composite material;
[0076] 0.7 g of the obtained sulfur-carbon composite material was mixed with 0.25 g of acetylene black by hand grinding in a mortar for 20 min, and then added to 10 g of polyacrylonitrile glue (the solvent was H2O, and the mass fraction of polyacrylonitrile was 5 wt % based on the mass of the polyacrylonitrile glue), stirred overnight to form a uniform slurry; the obtained slurry was coated on a carbon-coated aluminum foil with a scraper with a height of 75 μm, and then placed in a vacuum oven for drying at a temperature set to 70°C and a drying time of 10 h to obtain a sheet, which was cut into discs with a diameter of 12 mm to obtain a sulfur loading of 0.2 mg / cm 2 Sulfur-carbon negative electrode;
[0077] (2) Preparation of sodium ion positive electrode loaded with sodium supplement:
[0078] 0.7 g of sodium vanadium phosphate, 0.15 g of acetylene black and 0.21 g of Na2C4O4 were mixed by hand grinding in a mortar for 20 min, and then 2 g of polyacrylonitrile glue (the solvent was N-methylpyrrolidone, the mass fraction of polyacrylonitrile was 10 wt % based on the mass of the polyacrylonitrile glue) was added and stirred overnight to form a uniform slurry; the obtained slurry was coated on a carbon-coated aluminum foil with a scraper with a height of 350 μm, and then placed in a vacuum oven for drying at a temperature set at 70°C and a drying time of 10 h to obtain a sheet, which was cut into discs with a diameter of 12 mm to obtain a sodium vanadium phosphate loading of 3.0 mg / cm 2 The sodium ion positive electrode;
[0079] Mix 0.1g of sodium sulfide, 0.0125g of acetylene black and 0.42g of polyvinylidene fluoride (PVDF) glue (the solvent is N-methylpyrrolidone, the mass fraction of PVDF is 3wt% based on the mass of PVDF glue), stir overnight to form a uniform slurry; evenly coat the obtained slurry on the surface of the positive electrode material side of the obtained sodium ion positive electrode, and then put it into a vacuum oven for drying, the temperature is set to 70°C, the drying time is 10h, and a glass sodium ion positive electrode with a sodium supplement agent coated on the surface of one side of the positive electrode material layer is obtained;
[0080] (3) Assembling the sulfur-carbon negative electrode obtained in step (1), the sodium ion positive electrode loaded with a sodium supplement agent obtained in step (2), a polypropylene diaphragm and an electrolyte, and placing the surface of the sodium ion positive electrode loaded with the sodium supplement agent close to the polypropylene diaphragm to obtain a sulfur-based sodium ion battery with N / P (ratio of negative electrode capacity to positive electrode capacity) = 0.95.
[0081] Example 3
[0082] This embodiment provides a sulfur-based sodium ion battery, wherein the negative electrode of the sulfur-based sodium ion battery is a sulfur-carbon negative electrode, and the positive electrode is a sodium ion positive electrode loaded with a Na2C6H2O6 sodium supplement;
[0083] The sulfur-carbon negative electrode comprises a negative electrode current collector and a negative electrode material layer covered on the surface of the negative electrode current collector, wherein the negative electrode material comprises a sulfur-carbon composite material (composed of carbon nanotubes and a sulfur-containing mixture (composed of elemental S and ferrous sulfide in a mass ratio of 1:1) in a mass ratio of 90:5:5), conductive carbon black and polyvinylidene fluoride;
[0084] The sodium ion positive electrode includes a positive electrode current collector and a positive electrode material layer covered on the surface of the positive electrode current collector, wherein the positive electrode material layer includes sodium vanadium fluorophosphate, conductive carbon black and polyvinylidene fluoride in a mass ratio of 95:5:5; the Na2C6H2O6 sodium supplement is loaded between the positive electrode material layer and the positive electrode current collector away from the diaphragm of the sodium ion positive electrode, and the mass of the Na2C6H2O6 sodium supplement is 5% of the mass of the positive electrode active material in the sodium ion positive electrode;
[0085] The sulfur-based sodium ion battery also includes an electrolyte and a shell, and the electrolyte includes a sodium salt with a concentration of 0.5 mol / L and a fluoroethylene carbonate solvent.
[0086] The preparation method of the sulfur-based sodium ion battery is:
[0087] (1) Preparation of sulfur-carbon negative electrode:
[0088] The carbon nanotubes and the sulfur-containing mixture (the sulfur-containing mixture is composed of elemental S and ferrous sulfide in a mass ratio of 1:1) are mixed by wet grinding at a rotation speed of 500 rpm to obtain a mixture, wherein the reagent used in the wet grinding process is ethanol; the obtained mixture is vacuum dried in an oven for 24 hours, then taken out, and then placed in a glove box (O2<1ppm, H2O<1ppm), and then heated to 155°C in a muffle furnace and stored for 15 hours to prepare a sulfur-carbon composite material;
[0089] 0.9 g of the obtained sulfur-carbon composite material and 0.05 g of conductive carbon black were mixed by hand grinding in a mortar for 20 min, and then added to 10 g of polyvinylidene fluoride glue (the solvent was H2O, and the mass fraction of polyvinylidene fluoride was 0.5 wt % based on the mass of the polyvinylidene fluoride glue), stirred overnight to form a uniform slurry; the obtained slurry was coated on a carbon-coated aluminum foil with a scraper with a height of 75 μm, and then placed in a vacuum oven for drying, the temperature was set to 70°C, the drying time was 10 h, and a sheet was obtained. The obtained sheet was cut into discs with a diameter of 12 mm to obtain a sulfur loading of 0.3 mg / cm 2 Sulfur-carbon negative electrode;
[0090] (2) Preparation of sodium ion positive electrode loaded with sodium supplement:
[0091] Mix 0.1g sodium sulfide, 0.0125g acetylene black and 0.42g polyvinylidene fluoride (PVDF) glue (the solvent is N-methylpyrrolidone, the mass fraction of PVDF is 3wt% based on the mass of PVDF glue), stir overnight to form a uniform slurry; evenly coat the obtained slurry on the carbon-coated aluminum foil, and then put it into a vacuum oven for drying, the temperature is set to 70°C, and the drying time is 10h to obtain a carbon-coated aluminum foil coated with a sodium supplement layer;
[0092] 0.95 g of sodium vanadium fluorophosphate, 0.05 g of conductive carbon black and 0.0475 g of Na2C6H2O6 sodium supplement were mixed by hand grinding in a mortar for 20 min, and then 1 g of polyvinylidene fluoride glue (the solvent was N-methylpyrrolidone, and the mass fraction of polyvinylidene fluoride was 0.05 wt % based on the mass of the polyvinylidene fluoride glue) was added and stirred overnight to form a uniform slurry; the obtained slurry was coated on the sodium supplement layer of the carbon-coated aluminum foil coated with the sodium supplement layer with a scraper with a height of 350 μm, and then placed in a vacuum oven for drying, the temperature was set to 70°C, the drying time was 10 h, and a sheet was obtained. The obtained sheet was cut into discs with a diameter of 12 mm to obtain a sodium vanadium fluorophosphate loading of 3.9.mg / cm 2 The sodium ion positive electrode;
[0093] (3) Assembling the sulfur-carbon negative electrode obtained in step (1), the sodium ion positive electrode loaded with a sodium supplement agent obtained in step (2), a cellulose diaphragm and an electrolyte, and making the surface of the sodium ion positive electrode loaded with the sodium supplement agent away from the cellulose diaphragm, to obtain a sulfur-based sodium ion battery with N / P (ratio of negative electrode capacity to positive electrode capacity) = 1.0.
[0094] Example 4
[0095] This embodiment provides a sulfur-based sodium ion battery, such as Figure 1 As shown, the negative electrode of the sulfur-based sodium ion battery is a sulfur-carbon negative electrode, and the positive electrode is a sodium ion positive electrode loaded with a Na2C6H2O6 sodium supplement;
[0096] The sulfur-carbon negative electrode comprises a negative electrode current collector 1 and a negative electrode material layer 2 covered on the surface of the negative electrode current collector 1, wherein the negative electrode material comprises a sulfur-carbon composite material (composed of carbon nanotubes and a sulfur-containing mixture (composed of elemental S and ferrous sulfide in a mass ratio of 1:1) in a mass ratio of 90:5:5), conductive carbon black and polyvinylidene fluoride in a mass ratio of 1:1) in a mass ratio of 1.5:1;
[0097] The sodium ion positive electrode comprises a positive electrode current collector 3 and a positive electrode material layer 4 covered on the surface of the positive electrode current collector 3, wherein the positive electrode material layer 4 comprises sodium vanadium fluorophosphate, conductive carbon black and polyvinylidene fluoride in a mass ratio of 95:5:5; the Na2C6H2O6 sodium supplement is loaded in the positive electrode material layer 4 of the sodium ion positive electrode, and the mass of the Na2C6H2O6 sodium supplement is 5% of the mass of the positive electrode active material in the sodium ion positive electrode;
[0098] The sulfur-based sodium ion battery further comprises a glass fiber separator 5, an electrolyte and a shell, wherein the electrolyte comprises sodium trifluoromethanesulfonate and fluoroethylene carbonate solvent with a concentration of 0.5 mol / L.
[0099] The preparation method of the sulfur-based sodium ion battery is:
[0100] (1) Preparation of sulfur-carbon negative electrode:
[0101] The carbon nanotubes and the sulfur-containing mixture (the sulfur-containing mixture is composed of elemental S and ferrous sulfide in a mass ratio of 1:1) are mixed by wet grinding at a rotation speed of 500 rpm to obtain a mixture, wherein the reagent used in the wet grinding process is ethanol; the obtained mixture is vacuum dried in an oven for 24 hours, then taken out, and then placed in a glove box (O2<1ppm, H2O<1ppm), and then heated to 155°C in a muffle furnace and stored for 15 hours to prepare a sulfur-carbon composite material;
[0102] 0.9 g of the obtained sulfur-carbon composite material and 0.05 g of conductive carbon black were mixed by hand grinding in a mortar for 20 min, and then added to 10 g of polyvinylidene fluoride glue (the solvent was H2O, and the mass fraction of polyvinylidene fluoride was 0.5 wt % based on the mass of the polyvinylidene fluoride glue), stirred overnight to form a uniform slurry; the obtained slurry was coated on a carbon-coated aluminum foil with a scraper with a height of 75 μm, and then placed in a vacuum oven for drying, the temperature was set to 70°C, the drying time was 10 h, and a sheet was obtained. The obtained sheet was cut into discs with a diameter of 12 mm to obtain a sulfur loading of 0.3 mg / cm 2 Sulfur-carbon negative electrode;
[0103] (2) Preparation of sodium ion positive electrode loaded with sodium supplement:
[0104] 0.95 g of sodium vanadium fluorophosphate, 0.05 g of conductive carbon black and 0.0475 g of Na2C6H2O6 sodium supplement were mixed by hand grinding in a mortar for 20 min, and then 1 g of polyvinylidene fluoride glue (the solvent was N-methylpyrrolidone, and the mass fraction of polyvinylidene fluoride was 0.05 wt % based on the mass of the polyvinylidene fluoride glue) was added and stirred overnight to form a uniform slurry; the obtained slurry was coated on a carbon-coated aluminum foil with a scraper with a height of 350 μm, and then placed in a vacuum oven for drying at a temperature set to 70°C and a drying time of 10 h to obtain a sheet, which was cut into discs with a diameter of 12 mm to obtain a sodium vanadium fluorophosphate loading of 3.9 mg / cm 2 The sodium ion positive electrode;
[0105] (3) Assembling the sulfur-carbon negative electrode obtained in step (1), the sodium ion positive electrode loaded with a sodium supplement agent obtained in step (2), the cellulose separator 5 and the electrolyte to obtain a sulfur-based sodium ion battery with N / P (ratio of negative electrode capacity to positive electrode capacity) = 1.0.
[0106] Example 5
[0107] This embodiment provides a sulfur-based sodium ion battery, such as Figure 2 As shown, the negative electrode of the sulfur-based sodium ion battery is a sulfur-carbon negative electrode, and the diaphragm is a glass fiber diaphragm 5 loaded with a Na2S sodium supplement;
[0108] The sulfur-carbon negative electrode comprises a negative electrode current collector 1 and a negative electrode material layer 2 covered on the surface of the negative electrode current collector 1, wherein the negative electrode material comprises a sulfur-carbon composite material (composed of microporous carbon and S element in a mass ratio of 1:1) with a mass ratio of 80:10:10, acetylene black and sodium carboxymethyl cellulose;
[0109] The sodium ion positive electrode comprises a positive electrode current collector 3 and a positive electrode material layer 4 covered on the surface of the positive electrode current collector 3, wherein the positive electrode material layer 4 comprises sodium vanadium phosphate, acetylene black and polyvinylidene fluoride in a mass ratio of 80:10:10;
[0110] The surface of the glass fiber separator 5 facing the sodium ion positive electrode is covered with a sodium supplement layer 6, wherein the sodium supplement layer 6 contains a Na2S sodium supplement, and the mass of the Na2S sodium supplement is 12.5% of the mass of the sodium vanadium phosphate in the sodium ion positive electrode;
[0111] The sulfur-based sodium ion battery also includes an electrolyte and a shell, and the electrolyte includes sodium trifluoromethanesulfonate and fluoroethylene carbonate solvent with a concentration of 5 mol / L.
[0112] The preparation method of the sulfur-based sodium ion battery is:
[0113] (1) Preparation of sulfur-carbon negative electrode:
[0114] S and microporous carbon in a mass ratio of 1:1 were mixed by wet grinding at a rotation speed of 500 rpm to obtain a mixture, wherein the reagent used in the wet grinding process was ethanol; the obtained mixture was vacuum dried in an oven for 24 hours and then taken out, and then placed in a glove box (O2<1ppm, H2O<1ppm), and then heated to 155°C in a muffle furnace and stored for 15 hours to prepare a sulfur-carbon composite material;
[0115] 0.9 g of the obtained sulfur-carbon composite material and 0.05 g of acetylene black were mixed by hand grinding in a mortar for 20 min, and then added to 10 g of sodium carboxymethyl cellulose glue (the solvent was H2O, and the mass fraction of sodium carboxymethyl cellulose was 0.5 wt % based on the mass of the sodium carboxymethyl cellulose glue), stirred overnight to form a uniform slurry; the obtained slurry was coated on a carbon-coated aluminum foil with a scraper with a height of 75 μm, and then placed in a vacuum oven for drying at a temperature set to 70°C and a drying time of 10 h to obtain a sheet, which was cut into discs with a diameter of 12 mm to obtain a sulfur loading of 0.4 mg / cm 2Sulfur-carbon negative electrode;
[0116] (2) Preparation of sodium ion positive electrode:
[0117] 0.8 g of sodium vanadium phosphate and 0.1 g of acetylene black were mixed by hand grinding in a mortar for 20 min, and then 3.33 g of polyvinylidene fluoride (PVDF) glue (the solvent was N-methylpyrrolidone, and the mass fraction of PVDF was 3 wt % based on the mass of the PVDF glue) was added and stirred overnight to form a uniform slurry; the obtained slurry was coated on a carbon-coated aluminum foil with a scraper with a height of 350 μm, and then placed in a vacuum oven for drying at a temperature set at 70°C and a drying time of 10 h to obtain a sheet, which was cut into discs with a diameter of 12 mm to obtain a sodium vanadium phosphate loading of 5.9 mg / cm 2 The sodium ion positive electrode;
[0118] (3) Preparation of a membrane loaded with a sodium supplement:
[0119] 0.1 g of sodium sulfide, 0.0125 g of acetylene black and 0.42 g of polyvinylidene fluoride (PVDF) glue (the solvent is N-methylpyrrolidone, the mass fraction of PVDF is 3 wt % based on the mass of the PVDF glue), stirred overnight to form a uniform slurry; the obtained slurry is evenly coated on one side of the glass fiber diaphragm 5, and then placed in a vacuum oven for drying at a temperature set to 70° C. for a drying time of 10 h to obtain a glass fiber diaphragm 5 covered with a sodium supplement layer 6, that is, a glass fiber diaphragm 5 loaded with Na2S sodium supplement;
[0120] (4) Assembling the sulfur-carbon negative electrode obtained in step (1), the sodium ion positive electrode obtained in step (2), and the diaphragm loaded with the sodium supplement agent obtained in step (3), and making the surface of the diaphragm loaded with the sodium supplement agent face the sodium ion positive electrode, to obtain a sulfur-based sodium ion battery with N / P (ratio of negative electrode capacity to positive electrode capacity) = 0.97.
[0121] Example 6
[0122] This embodiment provides a sulfur-based sodium ion battery, which is the same as Example 1 except that the mass of the Na2S sodium supplement is 25% of the mass of the sodium vanadium phosphate in the sodium ion positive electrode, that is, the amount of Na2S in step (2) of the preparation method of the sulfur-based sodium ion battery is 0.2g.
[0123] Example 7
[0124] This embodiment provides a sulfur-based sodium ion battery, except that the Na2S sodium supplement is replaced by an equal mass of Na2CO3 sodium supplement, that is, the Na2S in step (2) of the preparation method of the sulfur-based sodium ion battery is replaced by an equal mass of Na2CO3, and the rest is the same as Example 1.
[0125] Example 8
[0126] This embodiment provides a sulfur-based sodium ion battery, except that the Na2S sodium supplement is replaced by an equal mass of Na2C2O4 sodium supplement, that is, the Na2S in step (2) of the preparation method of the sulfur-based sodium ion battery is replaced by an equal mass of Na2C2O4, and the rest is the same as Example 1.
[0127] Example 9
[0128] This embodiment provides a sulfur-based sodium ion battery, which is the same as Example 1 except that the Na2S sodium supplement is replaced by an equal mass of Na2O sodium supplement, that is, the Na2S in step (2) of the preparation method of the sulfur-based sodium ion battery is replaced by an equal mass of Na2O.
[0129] Example 10
[0130] This embodiment provides a sulfur-based sodium ion battery, which is the same as Example 1 except that the sodium vanadium phosphate in the sodium ion positive electrode is replaced by an equal mass of sodium ferric sulfate, that is, the sodium vanadium phosphate in step (2) of the preparation method of the sulfur-based sodium ion battery is replaced by an equal mass of sodium ferric sulfate.
[0131] Embodiment 11
[0132] This embodiment provides a sulfur-based sodium ion battery, which is the same as Embodiment 1 except that the sodium vanadium phosphate in the sodium ion positive electrode is replaced by an equal mass of sodium vanadium fluorophosphate, that is, the sodium vanadium phosphate in step (2) of the preparation method of the sulfur-based sodium ion battery is replaced by an equal mass of sodium vanadium fluorophosphate.
[0133] Example 12
[0134] This embodiment provides a sulfur-based sodium ion battery, except that the Na2S sodium supplement is replaced by an equal mass of Na2CO3 sodium supplement, that is, the Na2S in step (3) of the preparation method of the sulfur-based sodium ion battery is replaced by an equal mass of Na2CO3, and the rest is the same as Example 5.
[0135] Example 13
[0136] This embodiment provides a sulfur-based sodium ion battery, except that the Na2S sodium supplement is replaced by an equal mass of Na2C2O4 sodium supplement, that is, the Na2S in step (3) of the preparation method of the sulfur-based sodium ion battery is replaced by an equal mass of Na2C2O4, and the rest is the same as Example 5.
[0137] Embodiment 14
[0138] This embodiment provides a sulfur-based sodium ion battery, which is the same as Example 5 except that the Na2S sodium supplement is replaced by an equal mass of Na2O sodium supplement, that is, the Na2S in step (3) of the preparation method of the sulfur-based sodium ion battery is replaced by an equal mass of Na2O.
[0139] Embodiment 15
[0140] This embodiment provides a sulfur-based sodium ion battery, which is the same as Example 5 except that the sodium vanadium phosphate in the sodium ion positive electrode is replaced by an equal mass of sodium ferric sulfate, that is, the sodium vanadium phosphate in step (2) of the preparation method of the sulfur-based sodium ion battery is replaced by an equal mass of sodium ferric sulfate.
[0141] Example 16
[0142] This embodiment provides a sulfur-based sodium ion battery, which is the same as Example 5 except that the sodium vanadium phosphate in the sodium ion positive electrode is replaced by an equal mass of sodium vanadium fluorophosphate, that is, the sodium vanadium phosphate in step (2) of the preparation method of the sulfur-based sodium ion battery is replaced by an equal mass of sodium vanadium fluorophosphate.
[0143] Embodiment 17
[0144] This embodiment provides a sulfur-based sodium ion battery, which is the same as Example 1 except that the mass of the Na2S sodium supplement is 3% of the mass of the sodium vanadium phosphate in the sodium ion positive electrode, that is, the amount of Na2S sodium supplement added in step (2) of the preparation method of the sulfur-based sodium ion battery is reduced.
[0145] Embodiment 18
[0146] This embodiment provides a sulfur-based sodium ion battery, which is the same as Example 1 except that the mass of the Na2S sodium supplement is 40% of the mass of the sodium vanadium phosphate in the sodium ion positive electrode, that is, the Na2S sodium supplement added in step (2) of the preparation method of the sulfur-based sodium ion battery is increased.
[0147] Embodiment 19
[0148] The present embodiment provides a sulfur-based sodium ion battery, which is the same as Example 1 except that the sulfur-carbon composite material is composed of conductive carbon black and S element in a mass ratio of 0.1:1, that is, the mass ratio of the conductive carbon black and S element mixed in step (1) of the preparation method of the sulfur-based sodium ion battery is 0.1:1.
[0149] Comparative Example 1
[0150] This comparative example provides a sulfur-based sodium ion battery, which is the same as Example 1 except that the Na2S sodium supplement loaded in the sodium ion positive electrode is omitted, that is, the Na2S added in step (1) of the preparation method of the sulfur-based sodium ion battery is omitted.
[0151] The sulfur-based sodium ion batteries prepared in the above embodiments and comparative examples were subjected to three charge and discharge cycles at a current density of 0.05C in a matching potential window (the potential window matched by embodiments 1 to 2, 4 to 5, and 16 to 19 was 1.0 to 3.4 V, the potential window matched by embodiments 6 to 8 and 11 to 13 was 1.0 to 3.8 V, and the potential window matched by embodiments 3, 9 to 10 and 14 to 15 was 1.0 to 4.2 V), and then the cycle performance test was performed at a rate of 0.1C. The first cycle discharge specific capacity, average coulomb efficiency, and capacity retention rate after 100 cycles were obtained as shown in Table 1; wherein, the curves of the discharge specific capacity and coulomb efficiency of the sulfur-based sodium ion battery provided in Example 1 as a function of the number of cycles are shown in Table 1. Figure 3 As shown, the curve of the discharge specific capacity and coulombic efficiency of the sulfur-based sodium ion battery provided in Comparative Example 1 as a function of the number of cycles is shown in Figure 4 shown.
[0152] Table 1
[0153]
[0154]
[0155] From Table 1, we can get:
[0156] (1) The sulfur-based sodium ion batteries provided in Examples 1 to 16 simultaneously have a high first-cycle discharge specific capacity, a high average coulombic efficiency and excellent cycle stability; in the sulfur-based sodium ion batteries, using different sodium supplements, all achieved relatively significant effects; in the sulfur-based sodium ion batteries, when sodium iron sulfate and sodium vanadium fluorophosphate were used as positive electrode active materials, a high first-cycle discharge capacity could also be obtained; there was no significant difference in the electrochemical performance between the sulfur-based sodium ion battery with the sodium supplement coated on the diaphragm and the sulfur-based sodium ion battery with the sodium supplement loaded on the positive electrode side, indicating that loading the sodium supplement on the side of the diaphragm close to the positive electrode can also play a role in sodium supplementation;
[0157] (2) By comparing Example 1 with Examples 17 and 18, it can be seen that the percentage of the mass of the sodium supplement in the present invention to the mass of the positive electrode active material in the sodium ion positive electrode will affect the performance of the sulfur-based sodium ion battery; when the mass percentage of the sodium supplement is 5-30%, the sulfur-based sodium ion battery has a more excellent performance. This is because when the mass percentage of the sodium supplement is too high, the positive electrode resistance will increase, thereby causing the performance of the sulfur-based sodium ion battery to decrease. When the mass percentage of the sodium supplement is too low, it will not be able to play the role of sodium supplement, so that the large amount of sodium ions consumed by the sulfur-based sodium ion battery during the first round of film formation cannot be fully supplemented, resulting in a decrease in the performance of the sulfur-based sodium ion battery;
[0158] (3) By comparing Example 1 with Example 19, it can be seen that the mass ratio of the carbon-containing material to the sulfur and / or sulfide in the sulfur-carbon composite material of the present invention affects the performance of the sulfur-based sodium ion battery; when the mass ratio of the carbon-containing material to the sulfur and / or sulfide in the sulfur-carbon composite material is (0.5-1.5):1, the sulfur-based sodium ion battery has a more excellent performance, because the more carbon content, the better the conductivity, but too much leads to a decrease in energy density;
[0159] (4) By comparing Example 1 with Comparative Example 1, it can be seen that the sulfur-based sodium ion battery without a sodium supplement will consume a large amount of sodium ions during the first film formation, resulting in a lower average coulombic efficiency and a low specific capacity, and affecting the subsequent capacity. In the sulfur-based sodium ion battery provided by the present invention, the sodium supplement is loaded on the sodium ion positive electrode, and / or the sodium supplement is loaded on the surface of the membrane facing the sodium ion positive electrode to match the sulfur-carbon negative electrode. The sodium supplement in the sodium ion positive electrode loaded with the sodium supplement and / or the membrane loaded with the sodium supplement on the surface facing the sodium ion positive electrode can replenish the sodium ions that are irreversibly consumed on the positive electrode side during the first charging process, thereby improving the first discharge capacity, average coulombic efficiency and cycle performance of the sulfur-based sodium ion battery.
[0160] The above description is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention are within the protection scope and disclosure scope of the present invention.
Claims
1. A sulfur-based sodium ion battery, characterized in that: The negative electrode of the sulfur-based sodium ion battery is a sulfur-carbon negative electrode, the sodium ion positive electrode of the sulfur-based sodium ion battery is loaded with a sodium supplement, and / or the surface of the diaphragm of the sulfur-based sodium ion battery facing the sodium ion positive electrode is loaded with a sodium supplement.
2. The sulfur-based sodium ion battery according to claim 1, characterized in that: The sodium supplement agent is loaded on the sodium ion positive electrode in the following ways: distributed in the positive electrode material layer of the sodium ion positive electrode, and / or coated on the surface of the positive electrode material layer of the sodium ion positive electrode facing the diaphragm, and / or coated between the positive electrode material layer of the sodium ion positive electrode away from the diaphragm and the positive electrode current collector.
3. The sulfur-based sodium ion battery according to claim 1 or 2, characterized in that: The mass of the sodium supplement is 5-30%, preferably 8-12%, of the mass of the positive electrode active material in the sodium ion positive electrode.
4. The sulfur-based sodium ion battery according to any one of claims 1 to 3, characterized in that: The sodium supplement includes any one of metallic sodium powder, Na2S, Na2O, Na2C4O4, Na2C6O6, Na5TaO5, Na2C6H2O6, Na5VO5, NaNH2, Na2C2O4, Na2CO3, Na3VO4 or NaHF2, or a combination of at least two thereof.
5. The sulfur-based sodium ion battery according to any one of claims 1 to 4, characterized in that: The sodium ion positive electrode comprises a positive electrode current collector and a positive electrode material layer covered on the surface of the positive electrode current collector, wherein the positive electrode material layer comprises a sodium ion active material, a positive electrode conductive agent and a positive electrode binder.
6. The sulfur-based sodium ion battery according to claim 5, characterized in that: The mass ratio of the sodium ion active material, the positive electrode conductive agent and the positive electrode binder in the positive electrode material layer is (55-99):(0.5-15):(1-20).
7. The sulfur-based sodium ion battery according to any one of claims 1 to 6, characterized in that: The sulfur-carbon negative electrode comprises a negative electrode current collector and a negative electrode material layer covered on the surface of the negative electrode current collector, wherein the negative electrode material comprises a sulfur-carbon composite material, a negative electrode conductive agent and a negative electrode binder; Preferably, the mass ratio of the sulfur-carbon composite material, the negative electrode conductive agent and the negative electrode binder in the negative electrode material layer is (50-99): (0.5-30): (1-20); Preferably, the sulfur-carbon composite material comprises a carbon-containing material, and sulfur and / or sulfide, and the mass ratio of the carbon-containing material to sulfur and / or sulfide in the sulfur-carbon composite material is (0.2-2):
1.
8. The sulfur-based sodium ion battery according to any one of claims 1 to 7, characterized in that: The sulfur-based sodium ion battery also includes an electrolyte and a shell; Preferably, the electrolyte comprises a sodium salt and a solvent, and the solvent comprises any one of an ether solvent, an ester solvent or an ionic liquid solvent, or a combination of at least two of them.
9. A method for preparing a sulfur-based sodium ion battery according to any one of claims 1 to 8, characterized in that: The preparation method comprises: preparing a sulfur-carbon negative electrode comprising a sulfur-carbon composite material, preparing a sodium ion positive electrode loaded with a sodium supplement, and assembling the sulfur-carbon negative electrode and the sodium ion positive electrode into a sulfur-based sodium ion battery; or A sulfur-carbon negative electrode comprising a sulfur-carbon composite material is prepared, a diaphragm with a sodium supplement agent loaded on one side is prepared, and the sulfur-carbon negative electrode, the diaphragm loaded with the sodium supplement agent and the sodium ion positive electrode are assembled into a sulfur-based sodium ion battery, and the surface of the side of the diaphragm loaded with the sodium supplement agent is directed toward the sodium ion positive electrode; or A sulfur-carbon negative electrode comprising a sulfur-carbon composite material is prepared, a diaphragm with a sodium supplement agent loaded on one side is prepared, and a sodium ion positive electrode loaded with the sodium supplement agent is prepared. The sulfur-carbon negative electrode, the diaphragm loaded with the sodium supplement agent, and the sodium ion positive electrode loaded with the sodium supplement agent are assembled into a sulfur-based sodium ion battery, and the surface of the diaphragm loaded with the sodium supplement agent is directed toward the sodium ion positive electrode.
10. An electric device, characterized in that: The electric device comprises the sulfur-based sodium ion battery according to any one of claims 1 to 8.